(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This research is entitled "Deixis in Jinyoung Park Presentation about the New Vision and the Step JYP Entertainment". The purpose of this study is to find out what deixis are contained in Jinyoung Park’s presentation and to find out the deixis that Jinyoung Park used most often in his presentation. Researchers used qualitative research methods in this study. The research data comes from sentences containing deixis expressions in Jinyoung Park’s presentation. The source of the data in this study came from Jinyoung Park’s presentation video uploaded on youtube. In collecting data, researchers used observation techniques, namely organizing data and then analyzing the data that had been obtained, besides that researchers used documentation techniques, namely researchers downloaded data from the results of watching videos on youtube. The data were then analyzed using Levinson’s deixis theory. The results of this study indicate that the researcher found (226) deixis in Jinyoung Park’s presentation. Total person deixis (132), including first-person deixis (102), second-person deixis (8), and third-person deixis (22). In addition, place deixis has (15) deixis, time deixis (27), discourse deixis (18), the last is social deixis (34). The most dominant deixis in its presentation is personal deixis, totaling (132) deixis. The references in this presentation are mostly first-person plural, the most dominant word is "We" because the speaker mostly uses deictic words referring to himself and a group, he explains all the visions and new steps that will be developed together with related employees and investors.